Pengaruh Motivasi Belajar pada Pembelajaran Hybrid terhadap Hasil Belajar Matematika Siswa di Kelas VIII SMP Swasta PTPN IV Bah Jambi t.a.2022/2023 - Nur Intan Fazmi Ayu; Suprapto Manurung; Golda Novatrasio Sauduran (Journal on Education, 2023)
This research was conducted to pay attention to the low enthusiasm of students in students. This situation started with the Covid 19 situation that occurred from 2019 to 2022. This situation resulted in lessons at schools being carried out online. However, learning that is done online makes students learn less optimally. Many students do not do assignments from the teacher, many students are not present during online learning, and many students do not understand using learning applications such as Google, YouTube, Zoom, Google Classroom, Google Meet and others). In this case the researcher uses hybrid learning to determine student motivation. The purpose of this study was to find out the learning motivation in Hybrid learning towards the Mathematics Learning Outcomes of Students in Class VIII of PTPN IV Private Middle School ah Jambi T.A 2022/2023. This type of research was quantitative. The population in this study were all class VIII students of PTPN IV Private Middle School Bah Jambi T.A2022/2023. The sample in this study were students of class VIII-2. From the research data, the results of the normality test were obtained by using one sample komogorof to calculate learning motivation and also learning outcomes, the normality test for learning motivation N = 0.097 and the normality test for learning outcomes N = 0.013. From the results of hypothesis testing obtained t count = 1.891 and t table = 1.701. So if it is known based on the t table with a significance level of α = 0.05 the results show that 1.891 > 1.701. This means that t count is greater than t table. it can be concluded that there is an influence of learning motivation on students' mathematics learning outcomes in class VIII of PTPN IV Bah Jambi Private Middle School T.A 2022/2023. This is also reinforced because Hybrid learning has advantages and goals that are able to invite students to learn more actively, because they focus on online learning and students are able to use learning applications.